On the interaction of the scalar field with a Coulomb-type potential in a spacetime with a screw dislocation and the Aharonov-Bohm effect for bound states - Vitória, R. L. L.; Bakke, K. (European physical journal plus, 2018)
. We investigate topological effects on the interaction of a scalar field with a Coulomb-type potential in a spacetime with a screw dislocation (space-like dislocation). We also consider the topological defect with an internal magnetic field. Later, we investigate the interaction of a scalar field with a Coulomb-type potential plus another Coulomb-type potential (gauge potential), a uniform magnetic field, the Klein-Gordon oscillator and a linear scalar potential in this topological defect spacetime. Then, by searching for analytical solutions to the Klein-Gordon equation in the spacetime with a screw dislocation, we obtain analogues effects of the Aharonov-Bohm effect for bound states.